Gender Inclusive Nuclear Regulatory Body of Pakistan - Noreen Iftakhar; Shazia Fayyaz (International Journal of Nuclear Security, 2022)
A gender-inclusive workplace considers, recognizes, and promotes the skills and potential of both men and women, irrespective of their gender, race, ethnicity, ability, and age. In Pakistan, women in the workforce are increasing day by day and women are achieving higher positions at a corporate level. Nevertheless, the nuclear field is still generally considered a male oriented field. This paper aims to break the misconception and analyze gender inclusion in the nuclear regulatory body of Pakistan. The paper explores contours of gender inclusion in the Pakistan Nuclear Regulatory Authority (PNRA) by shedding light on female's representation in different management positions as well as in working level technical and non-technical committees. The paper study also highlights the steps PNRA management has taken, over the years, to ensure a conducive environment for the female workforce and provisions for an equal learning opportunity to enhance their competence.
Keywords: Gender Inclusive; Regulatory Body; Pakistan; PNRA